Early warning indicators: Financial and macroeconomic imbalances in Central and Eastern European countries - Orsolya Csortos; Zoltán Szalai (Magyar Nemzeti Bank, 2014)
In this paper we apply the Early Warning System methodology to ten Central and Eastern European Countries to find useful sets of indicators which could predict macroeconomic and financial imbalances. We argue that finding such indicators is crucial in the current monetary policy framework because significant imbalances could build up without any sign of risk to price stability. We examine the stylised behaviour of the most important macroeconomic variables over the business cycle and select the most preferred indicator variables. Our methodology consists of choosing the most useful combination of variables in terms of false alarms and misses, taken as given the preferences of the decision maker in terms of committng various types of errors. We find, that a certain combination of the global financial variable, the real exchange rate, capital flows and credit is a plausible signal macroeconomic imbalances. The results suggest that although the above indicators should not be used mechanically, they could usefully complement analytical tools available to modern central banks.
Keywords: E32; E37; E44; E58; 330; early warning indicators; signalling approach; macroeconomic stability; financial stability; monetary policy strategy